The Fate of Contaminants of Emerging Concern in an Upflow Anaerobic Sludge Blanket Reactor Coupled with Constructed Wetlands for Decentralized Domestic Wastewater Treatment - Evridiki Barka; Asimina Koukoura; Evangelos Statiris; Taxiarchis Seintos; Athanasios S. Stasinakis; Daniel Mamais; Simos Malamis; Constantinos Noutsopoulos (Molecules)
Removal of micropollutants using biological treatment systems remains a challenge, since conventional bioprocess systems require adaptations to provide more advanced treatment. An ambient temperature upflow anaerobic sludge blanket (UASB) reactor was employed, followed by a two-stage (saturated and unsaturated) vertical subsurface flow (VSSF) constructed wetland (CW) system, to treat domestic wastewater from a nearby settlement and investigate the occurrence and fate of 10 contaminants of emerging concern (CECs) in decentralized, non-conventional treatment systems. The integrated UASB—two-stage CW system achieved high performance regarding abatement of target CECs across all periods. Removal efficiencies ranged from 78% ± 21% (ketoprofen) to practically 100% (2-hydroxybenzothiazole). The pilot system was found to be robust performance-wise and provided enhanced treatment in comparison to a conventional wastewater treatment plant operating in parallel. Most of the target CECs were successfully treated by UASB, saturated and unsaturated CWs, while ibuprofen, bisphenol A and diclofenac were mostly removed in the unsaturated CW. Environmental risk assessment revealed that triclosan poses a significant ecological risk to algae during treated wastewater disposal into the aquatic environment. Additionally, cumulative risk quotient indicated that the potential for mixture toxicity should be carefully considered across all trophic levels.